Alkaloid quantitation and chemical fingerprinting of Icelandic Huperzia selago genotypes using HPLC-UV and UPLC-QToF-MS - Magnea Guðmundsdóttir 1982- (2020)
Plants belonging to the family Lycopodiaceae (clubmosses) produce bioactive lycopodium alkaloids. The clubmoss Huperzia serrata has been used as herbal medicine for centuries in China for numerous of ailments, e.g., fever, swelling, and to improve memory. The alkaloid, huperzine A (hupA), was first isolated from the whole plant of H. serrata and has been shown to be a potent acetylcholinesterase inhibitor and of interest for development of drugs for Alzheimer’s. A related species, Huperzia selago, which grows in Iceland, produces considerable amounts of hupA amongst eleven other lycopodium alkaloids reported so far. The aim of this study was to characterize alkaloid variations of the three Icelandic H. selago genotypes. The specific objectives were to determine the hupA contents using HPLC-UV and assess its variation in genotypes and to explore the use of UPLC-MS alkaloid fingerprinting in the recognition of genotypes. The Icelandic H. selago was found to have a wide range of hupA contents from 41 μg/g d.w. to 649 μg/g d.w. in the three genotypes, determined by a HPLC-UV method. Genotype 3 contains significantly higher hupA than genotype 1 and the highest amount of hupA was determined in one specimen of genotype 3 (649 μg/g d.w.). Alkaloid fingerprinting was performed using a UPLC-MS method. Principal component analysis (PCA) fingerprinting data reveals that alkaloid profile tends to be genotype specific. From the PCA loading plot, hupA and hupB are driving the separation of genotype 3 from the other two. It is suggested that Icelandic H. selago of genotype 3 is a good alternative source for natural hupA. This study highlights the importance of chemical fingerprinting and thorough plant identification in the selection of medicinal plant raw material with highest pharmaceutical interest. Jurtir af jafnaætt (Lycopodiceae) framleiða meðal annars lífvirka lýkópódíum alkalóíða. Huperzia serrata er jafni sem hefur verið notaður í Kína til náttúrulækninga svo öldum skiptir, meðal annars sem hitalækkandi, ...